The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1021/acs.cgd.0c00981
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Structural, Energetic, and Spectroscopic Properties of MoS3 Polymorphs

Abstract: In spite of the interest of a-MoS 3 based nanomaterials, the amorphous nature of the MoS 3 phase makes it challenging to control and understand its chemical reactivity. In particular, the type of the structural building unit such as Mo 3 triangular vs Mo chain is still debated, while the ambivalent interpretation of the nature of sulfur species (S 2− , S 2 2− ) and Mo−Mo bonds leads to ambiguous interpretations of spectroscopic data and reactivity. By density functional theory (DFT), we simulate the energetic,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 65 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…1 The demand for amorphous materials is also increasing due to the important characteristics essential for industrial applications with the addition of emerging elds. 2 Calcium phosphate is an important compound not only for biomedical applications but also for industrial applications, and the main compounds include hydroxyapatite, b-tricalcium phosphate, a-tricalcium phosphate, tetra-calcium phosphate, dicalcium phosphate, dicalcium phosphate monohydrate, triple superphosphate, etc. [3][4][5] Hydroxyapatite (Hap) is a wellknown bio-ceramic that has structural similarities with human hard tissue.…”
Section: Introductionmentioning
confidence: 99%
“…1 The demand for amorphous materials is also increasing due to the important characteristics essential for industrial applications with the addition of emerging elds. 2 Calcium phosphate is an important compound not only for biomedical applications but also for industrial applications, and the main compounds include hydroxyapatite, b-tricalcium phosphate, a-tricalcium phosphate, tetra-calcium phosphate, dicalcium phosphate, dicalcium phosphate monohydrate, triple superphosphate, etc. [3][4][5] Hydroxyapatite (Hap) is a wellknown bio-ceramic that has structural similarities with human hard tissue.…”
Section: Introductionmentioning
confidence: 99%
“…We have simulated Mo 3 S 9−x nanoclusters as a representative active site structure for small nanoparticles of MoS 3 (see Figure 1a) as proposed in our previous study on a-MoS 3 . 21 The Mo 3 S 9−x nanoclusters are positioned on a graphite support model at the location of a Stone−Wales defect, which has been introduced to mimic an anchoring point. Orientations of the nanocluster were explored using DockOnSurf, specifying the Stone−Wales defect as the adsorption site and various sulfur atoms as anchoring points.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, all these active sites might interconvert as suggested by in situ Raman measurements: bridging S 2 2– species may convert into top S 2 2– species and can then create unsaturated Mo-sites . DFT simulations of S–S vibrational frequencies for various neutral a -MoS 3 polymorphs suggested that some of these interpretations should be considered with care, as they relied on a questionable assignment of the top and bridging S 2 2– species in a -MoS 3 through infrared (IR) or Raman spectroscopies using charged thiomolybdate clusters as references. Indeed, the complex structure of the a -MoS 3 phase has been debated for many years. The DFT study by Sahu et al revealed that large sizes of neutral a -MoS 3 polymers favor distorted Mo chain-like structures, while smaller entities with Mo triangular moieties are more stable .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations